Thyroid disorders in obese patients. Does insulin resistance make a difference? - Nicoleta Răcătăianu; Nicoleta Leach; Cosmina Ioana Bondor; Smaranda Mârza; Daniela Moga; Ana Valea; Cristina Ghervan (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: The aim of this study was to evaluate the association between insulin resistance and thyroid pathology in obese patients, and compare the results between insulin-resistant and noninsulin-resistant patients. Subjects and methods: Obese/nondiabetic patients, aged 18-70 years, attending the outpatient endocrinology service for 2 years were consecutively included. We evaluated the patients' fasting plasma glucose, insulin, homeostasis model assessment of insulin resistance index (HOMA-IR), thyroid-stimulating hormone (TSH), free thyroxine (FT4), antithyroperoxidase antibodies (TPO-Ab), antithyroglobulin antibodies (Tg-Ab), and thyroid ultrasound. Results: We included 82 patients with a mean age 44.21 ± 12.67 years. The thyroid disorders encountered and their prevalences were: hypothyroidism (14.6%, 95% confidence interval [CI] 8.6-23.8%), hyperthyroidism (1.2%, 95% CI 2.0-6.6%), goiter (28.0%, 95% CI 19.5-3.6%), thyroid nodules (35.4%, 95% CI 25.9-46.2%), and Hashimoto's thyroiditis (32.9%, 95% CI 23.7-43.7%). HOMA-IR correlated positively with TSH levels (r = 0.24, p = 0.028), and this correlation remained after adjustment for body mass index (BMI), waist/hip ratio (WHR), serum cortisol, subcutaneous fat thickness (SFT), visceral fat thickness (VFT), triglycerides, γ-glutamyl transpeptidase (GGT), and alanine aminotransferase (ALT) in multivariate regression analysis (b = 0.207, 95% CI, 0.09-0.385, p = 0.023). TSH levels were significantly higher in patients with HOMA-IR ≥ 2.5 than in those with HOMA-IR < 2.5 (2.03 μIU/mL, interquartile range [IQR] 1.59-2.69 μIU/mL) versus 1.59 μIU/mL, IQR 0.94-2.26 μIU/mL, p = 0.023). Conclusions: The most prevalent thyroid disorder in patients attending our endocrinology clinic for investigation of obesity was thyroid nodules. One in seven patients had hypothyroidism. Our findings suggest that TSH levels correlate with insulin resistance in obese patients.